Penyusunan Laporan Keuangan UMKM Bakso Bakar Rahmat Berdasarkan SAK EMKM (Studi Kasus Pada UMKM Pedagang Bakso Bakar Rahmat Di Kota Binjai, Kecamatan Binjai Barat) - Aprilia, Fista Lindu; Marshanda; Salsabilla, Echa; Kania, Sherly Indah; Franita, Riska (CV. ITTC INDONESIA, 2025)
The preparation of the financial statements of UMKM Bakso Bakar Rahmat for the period 2023 was carried out using qualitative methods. Primary data sources come from interview data and are better managed by researchers based on SAK EMKM. Based on the results of the interview, the preparation of financial statements was measured very simply. The preparation of financial statements has not met the SAK EMKM standards. This study aims to assist UMKM Bakso Bakar Rahmat in preparing financial statements based on SAK EMKM. Financial statements based on SAK EMKM are measured by calculating assets, liabilities (obligations), equity, income, and expenses. Based on the results of the research, the net profit obtained was IDR 162,266,748 per year and the net profit in a month was IDR 13,522,229. So it is concluded that UMKM Bakso Bakar Rahmat has a financial performance that is not good enough with obstacles in the preparation of financial reports that are not in accordance with PSAK standards. With that, researchers help prepare financial reports based on SAK EMKM to assess financial performance better in the future.